2011
DOI: 10.1029/2011gl046827
|View full text |Cite
|
Sign up to set email alerts
|

Extreme waves in random crossing seas: Laboratory experiments and numerical simulations

Abstract: [1] We present an experimental and numerical investigation on the statistical properties of the surface elevation in crossing sea conditions. Experiments are performed in a very large wave basin (70 m × 50 m × 3 m) and numerical results are obtained using a higher order method for solving the Euler equations. Both experimental and numerical results indicate that the number of extreme events depends on the angle between the two interacting systems. This outcome is supported by recent theoretical investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 18 publications
10
59
0
1
Order By: Relevance
“…Onorato et al (2006a) proposed a system of two coupled nonlinear Schrödinger equations (CNLS) to explain the formation of wave extremes in crossing seas (see also Shukla et al, 2006), showing that the second wave train advancing at a certain critical angle facilitates the modulational instability. These findings are validated by numerical simulations of the Euler equations, as well as by laboratory experiments (Onorato et al, 2010;Toffoli et al, 2011). It has also been found that the coefficient of kurtosis increases up to 40 • of crossing between the wave trains and then stabilizes, reaching a maximum between 40 and 60 • .…”
Section: P G Petrova and C Guedes Soares: Distributions Of Nonlinesupporting
confidence: 60%
See 1 more Smart Citation
“…Onorato et al (2006a) proposed a system of two coupled nonlinear Schrödinger equations (CNLS) to explain the formation of wave extremes in crossing seas (see also Shukla et al, 2006), showing that the second wave train advancing at a certain critical angle facilitates the modulational instability. These findings are validated by numerical simulations of the Euler equations, as well as by laboratory experiments (Onorato et al, 2010;Toffoli et al, 2011). It has also been found that the coefficient of kurtosis increases up to 40 • of crossing between the wave trains and then stabilizes, reaching a maximum between 40 and 60 • .…”
Section: P G Petrova and C Guedes Soares: Distributions Of Nonlinesupporting
confidence: 60%
“…These results actually confirm the fact that the large shift between the main directions of the component wave systems in a mixed sea suppresses the modulational instability. Consequently, one encounters smaller wave amplitudes and heights at the lowest probability levels of the distribution tails, as already reported for numerically simulated waves (Onorato et al, 2006a;Shukla et al, 2006;Onorato et al, 2010;Toffoli et al, 2011) for waves modelled from the second-order theory (Toffoli et al, 2006), or in laboratory experiments (Toffoli et al, 2011). The most favourable angles of crossing for the occurrence of large wave events are reported to be in the range between 10 and 40 • .…”
Section: Probability Distributions Of Wave Crests and Troughssupporting
confidence: 50%
“…Onorato et al (2009) and Toffoli et al (2010) performed experiments and numerical analysis of irregular crossing waves, observing a direct relationship between crossing angle and kurtosis, an indicator of the probability of freak wave occurrence. All of the experimental studies that we are aware of have been limited to small degrees of directional spreading and have not observed the formation of a set-up, with the exception of Toffoli et al (2011), who did conduct experiments with crossing wave systems at crossing angles up to 40…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the study methods on rogue waves mainly focus on theoretical analysis (Onorato et al, 2006a, b), numerical simulation (Tao et al, , 2012a, physical experiment (Toffoli et al, 2010(Toffoli et al, , 2011) and field observations. Some key advances were reviewed by Dysthe et al (2008) and Kharif et al (2009).…”
Section: Introductionmentioning
confidence: 99%